Islamizing the Management of Human Resources in Schools: The Imperative for Muslim Proprietors of Schools - Adebayo, Rafiu Ibrahim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2015)
The proliferation of institutions of learning established by Muslim organizations and individuals could be said to be a welcome development though they are yet to compete numerically with those established by Christian organizations and individuals. However, it is observed that many of these institutions are only recognized to be Islamic by their names as there is hardly any difference between their operation and the secular ones. This paper identifies and discusses some principles which will make Muslim schools really Islamic in nature and operation. Proprietors of these schools therefore need to be up and doing in the task of planning, organizing, leading, coordinating, directing, supervising, controlling, evaluating and reporting roles for their schools to be real Muslim schools. These tasks can only be accomplished when human resources in schools are properly managed in the Islamic manner.